The Patriarch - Walker, Martin, 1947 January 23- (Walker, Martin, 1947 January 23- Bruno series, 2016)
Attending the lavish birthday celebration of a World War II hero, police chief Bruno becomes intimately tangled in the family's dynamics when one of their close friends dies under suspicious circumstances.